Haemophilus influenzae meningitis 5 years after introduction of the Haemophilus influenzae type b conjugate vaccine in Brazil - Ribeiro, Guilherme S. (2007)
The long-term impact of Haemophilus influenzae type b (Hib) conjugate vaccine, introduced throughout Latin America in the late 1990s, has not been evaluated. Active surveillance for H. influenzae meningitis was performed from August 9, 1996 to August 8, 2004 in Metropolitan Salvador, Brazil. Five years after the introduction of Hib conjugate vaccine, Hib meningitis incidence decreased from 2.39 to 0.06 cases per 100,000 population (98%) overall, and from 60.9 to 3.1 cases per 100,000 population (95%) in children <1 year of age. A transient serotype replacement phenomenon was observed associated with a small increase of meningitis due to two H. influenzae type a clonal groups. These findings indicate that Hib immunization campaign has led to the virtual elimination of Hib disease in this region.